Outcomes of COVID‐19‐positive acute coronary syndrome patients: A multisource electronic healthcare records study from England - Rashid, Muhammad; Wu, Jianhua; Timmis, Adam; Curzen, Nick; Clarke, Sarah; Zaman, Azfar; Nolan, James; Shoaib, Ahmad; Mohamed, Mohamed O; Belder, Mark A.; Deanfield, John; Gale, Chris P.; et al. (Journal of internal medicine, 2021)
Background Patients with underlying cardiovascular disease and coronavirus disease 2019 (COVID‐19) infection are at increased risk of morbidity and mortality. Objectives This study was designed to characterize the presenting profile and outcomes of patients hospitalized with acute coronary syndrome (ACS) and COVID‐19 infection. Methods This observational cohort study was conducted using multisource data from all acute NHS hospitals in England. All consecutive patients hospitalized with diagnosis of ACS with or without COVID‐19 infection between 1 March and 31 May 2020 were included. The primary outcome was in‐hospital and 30‐day mortality. Results A total of 12 958 patients were hospitalized with ACS during the study period, of which 517 (4.0%) were COVID‐19‐positive and were more likely to present with non‐ST‐elevation acute myocardial infarction. The COVID‐19 ACS group were generally older, Black Asian and Minority ethnicity, more comorbid and had unfavourable presenting clinical characteristics such as elevated cardiac troponin, pulmonary oedema, cardiogenic shock and poor left ventricular systolic function compared with the non‐COVID‐19 ACS group. They were less likely to receive an invasive coronary angiography (67.7% vs 81.0%), percutaneous coronary intervention (PCI) (30.2% vs 53.9%) and dual antiplatelet medication (76.3% vs 88.0%). After adjusting for all the baseline differences, patients with COVID‐19 ACS had higher in‐hospital (adjusted odds ratio (aOR): 3.27; 95% confidence interval (CI): 2.41–4.42) and 30‐day mortality (aOR: 6.53; 95% CI: 5.1–8.36) compared to patients with the non‐COVID‐19 ACS. Conclusion COVID‐19 infection was present in 4% of patients hospitalized with an ACS in England and is associated with lower rates of guideline‐recommended treatment and significant mortality hazard.